Investigation of intraregional variation, grape amino acids, and pre-fermentation freezing on varietal thiols and their precursors for Vitis vinifera Sauvignon blanc. (15th October 2019) - Chen, Liang; Capone, Dimitra L.; Nicholson, Emily L.; Jeffery, David W.
Abstract: Sauvignon blanc grape samples (n = 21) from across a single Geographical Indication of South Australia were analysed for thiol precursors and amino acids, and fermented in an identical laboratory-scale fermentation trial to investigate the intraregional pattern of varietal thiols in the wines. Precursors and thiols exhibited obvious intraregional diversity, and notably, stronger correlations were observed between a number of amino acids and thiol precursors (especially with glutamic acid, r  ≤ −0.73) rather than free thiols. Additionally, pre-fermentation freezing (−20 °C, 1 month) was applied to five selected fresh grape samples and their juices, followed by identical fermentation. In comparison to wines from fresh grapes or frozen juices, significant elevation of varietal thiols (up to 10-fold) occurred in the wines derived from frozen grapes, with parallel increases of precursors (up to 19-fold) in juices from frozen berries. These novel results may lead to new strategies for thiol enhancement during winemaking.